2020
DOI: 10.1093/braincomms/fcaa090
|View full text |Cite
|
Sign up to set email alerts
|

Differential cross-seeding properties of tau and α-synuclein in mouse models of tauopathy and synucleinopathy

Abstract: Abstract Co-occurrence of tau and α-synuclein pathologies in a subset of Alzheimer’s disease patients has led to the idea that mixed pathologies may play a unique characteristic role in the Alzheimer’s disease neurodegenerative cascade. To understand the etiology of such mixed pathologies, we investigated cross-seeding by human recombinant tau and human recombinant α-synuclein fibrillar species in a mouse model of tauopathy (Line PS19) or synucleinopathy (Line M2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 54 publications
0
27
1
Order By: Relevance
“…It is likely that Alzheimer co-pathology contributes towards the development of dementia in Lewy-body positive cases, since two concomitant neurodegenerative diseases are most likely worse than one. Moreover, in vitro and in vivo studies have shown that amyloid-␤ and tau fibrils can induce ␣-synuclein monomers to aggregate [112,113]. Approximately 10% of cognitively normal people at 50 years are amyloid-␤ positive, rising to 33% at 80 years [114].…”
Section: The Soc Model Predicts Differences In Cognitive Declinementioning
confidence: 99%
“…It is likely that Alzheimer co-pathology contributes towards the development of dementia in Lewy-body positive cases, since two concomitant neurodegenerative diseases are most likely worse than one. Moreover, in vitro and in vivo studies have shown that amyloid-␤ and tau fibrils can induce ␣-synuclein monomers to aggregate [112,113]. Approximately 10% of cognitively normal people at 50 years are amyloid-␤ positive, rising to 33% at 80 years [114].…”
Section: The Soc Model Predicts Differences In Cognitive Declinementioning
confidence: 99%
“…Treatment of oligodendrocytes and its precursors with exogenous α-Syn aggregates increases the low level of endogenous α-Syn by templating the formation of stable α-Syn aggregates [44,44,65], and this has been hypothesised to represent a neuron-oligodendroglial pathway of importance for MSA [43]. MSA brain extracts and in particular the detergent-insoluble fraction containing the α-Syn filaments are more potent seeds of α-Syn aggregation in cellular and in vivo models [79,89,108,114,115]. This potency can be propagated in laboratory animals and is one reason why MSA has been proposed to represent a distinct prion-like disease [79,108,114,115].…”
Section: Introductionmentioning
confidence: 99%
“…MSA brain extracts and in particular the detergent-insoluble fraction containing the α-Syn filaments are more potent seeds of α-Syn aggregation in cellular and in vivo models [79,89,108,114,115]. This potency can be propagated in laboratory animals and is one reason why MSA has been proposed to represent a distinct prion-like disease [79,108,114,115]. Mounting evidence supports that the α-Syn aggregation in oligodendrocytes represents the key to MSA brain extracts being potent inducers of α-Syn aggregation in disease models [77].…”
Section: Introductionmentioning
confidence: 99%
“…482 Fibrils composed from both Tau and a-synuclein monomers showed differential pathology propagation when injected into the mouse brain, where Tauopathy was induced at higher levels than synucleinopathy. 483 Both Tau and a-synuclein have been implicated in pathology spreading through anatomically connected brain regions in a protein strain-specific manner, resulting in distinct disease phenotypes in humans (reviewed in ref. 484 and 485).…”
Section: Is Heparin a Major Structural Component Of Tau Fibrils?mentioning
confidence: 99%